Composição nutricional de dietas com alegações detoxificantes em sites vinculados na mídia - Lagunaz, Letícia (My University, 2019)
Among fashionable diets, the "detox" diet has gained popularity amid the search for perfect bodies, detoxifying claims and short-term slimming. The objective of this work was to analyze the nutritional composition of detoxification diets on linked sites in the media. Materials and Methods: A descriptive cross-sectional study of selected detoxification diets was performed on non-scientific media. Diets were calculated through the Diet Win 2008 program and compared to the recommendations proposed by the DRIs (Dietary Reference Intakes) for macronutrients and micronutrients. For the calculation of diets, recommendations for adults aged 19 to 50 years were adopted as standard. The analysis of the nutritional composition of diets with detoxifying claim showed a mean with low daily energy value. Most diets are adequate for protein and magnesium recommendations, but some seem to be deficient in carbohydrates, lipids, fibers and other micronutrients. The most frequent foods in diets were fruits and vegetables. Conclusion: The diets published in non-scientific journals present inadequacies in the distribution of macronutrients and micronutrients, therefore, these diets are unsafe options for healthy weight loss, therefore the importance of a professional in the field to be able to individualize diets and weight loss strategies in a healthy and lasting way. [resumo fornecido pelo autor]
Entre as dietas da moda, a dieta "detox" tem ganho popularidade em meio a busca por corpos perfeitos, por alegações desintoxificantes e emagrecimento a curto prazo. O objetivo deste trabalho foi analisar a composição nutricional de dietas de detoxificação em sites vinculados na mídia. Materiais e Métodos: Foi realizado um estudo do tipo transversal descritivo sobre dietas de detoxificação selecionadas em mídias não científicas. As dietas foram calculadas através do programa Diet Win 2008 e comparadas às recomendações propostas pelas DRIs (Dietary Reference Intakes) para macronutrientes e micronutrientes. Para o cálculo das dietas, foram adotadas como padrão as recomendações para adultos com a faixa etária de 19 a 50 anos. A análise da composição nutricional das dietas com alegação detoxificante demonstrou uma média com baixo valor energético diário. A maioria das dietas está adequada às recomendações de proteínas e magnésio, porém algumas parecem estar deficientes em carboidratos, lipídeos, fibras e demais micronutrientes. Os alimentos mais frequentes nas dietas foram frutas e verduras. Conclusão: As dietas publicadas em revistas não científicas apresentam inadequações na distribuição de macronutrientes e micronutrientes, portanto, estas dietas são opções inseguras para o emagrecimento saudável, por isso a importância de um profissional da área para poder individualizar dietas e estratégias de emagrecimento de forma saudável e duradoura. [resumo fornecido pelo autor]
Keywords: Alimentos - Composição; Dieta; Redes sociais on-line